PENERAPAN PENDIDIKAN KARAKTER MELALUI REWARD DAN PUNISHMENT DALAM MENINGKATKAN MOTIVASI BELAJAR AGAMA ISLAM DI SMA NEGERI 9 MALANG - Fairuz Zabadi Anieq Ahmad; Rosichin Mansur; Kukuh Santoso (VICRATINA, 2021)
Based on information in the field, some educators ignore small things that can increase students' interest and enthusiasm for learning. The existence of rewards and punishments is expected to overcome students' problems in learning, learning motivation also plays a major role in shaping the character of students. The purpose of this study was to describe the role of reward and punishment as well as the supporting and inhibiting factors in increasing motivation and learning outcomes in Islamic religious education subjects at SMAN 9 Malang. This research uses descriptive qualitative methods and case studies. The data analysis used is interactive data analysis. The form of the application of rewards in increasing learning motivation in Islamic religious education subjects at SMAN 9 Malang is an appreciation for students who do not violate the rules in the form of adding character values, while the form of punishment is for students who do not attend the dhuha prayer congregation and literacy will get a punishment in the form of clean the school environment. The supporting and inhibiting factors in the application of reward and punishment in increasing learning motivation in Islamic religious education subjects at SMAN 9 Malang is the presence or absence of supporting facilities and infrastructure.